Functional Hallucinations in Schizophrenia Responding to Adjunctive Sodium Valproate - Rajkumar, Ravi Philip (Medknow Publications & Media Pvt Ltd, 2012)
Functional hallucinations are a rare phenomenon, wherein hallucinations are triggered by a stimulus in the same modality, and co-occur with it. Although hallucinations in schizophrenia are normally treated using antipsychotics, not all patients respond to them. The following is the report of a patient with paranoid schizophrenia who experienced persistent functional hallucinations, triggered by the sound of machines in his factory, in the absence of other psychotic symptoms. These occurred despite adequate doses of risperidone, which had controlled his other symptoms. The addition of sodium valproate, titrated up to 1700 mg/day based on response and tolerability, resulted in a marked improvement in this phenomenon and enabled him to return to work. The implications and possible mechanisms of the patient's response are discussed.